PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT BANK NEGARA INDONESIA (Persero), Tbk CABANG RENGAT - Luthfi Maadjid Abdullah; Alex Winarno (Universitas Bina Taruna Gorontalo, 2022)
This study intends to explore the influence of work motivation and work discipline on employee performance at Bank Negara Indonesia Rengat Branch. It employs a descriptive-causality quantitative approach. A saturated sample was utilized to draw data from the study's 55 participants, all of whom worked for PT Bank Negara Indonesia Branch Rengat. Multiple linear regression analysis was done to assess the data. The Tbk Rengat Branch of PT Bank Negara Indonesia (Persero) seeks to succeed in the highly competitive banking business. Bank Negara Indonesia Rengat Branch is particularly concerned about staff performance, as can be observed by its attempts to encourage performance improvement. According to figures obtained in 2019 and 2020, there has been a drop in performance. The results of the research of work motivation and work discipline impact the performance of workers of PT Bank Negara Indonesia (Persero) Tbk Rengat Branch by 53.9 percent partially and concurrently.